UPAYA ORANG TUA DALAM MENGEMBANGKAN KREATIVITAS ANAK TUNAGRAHITA - Andesriza, Vyolita - (Bimbingan dan Konseling, 2014)
This research was caused because of there are still many parents that were feel ashamed because of the unability of their children. Though they were actually also have many anique ability than the normal children. Besides, many parents are less of care in their children growth and hold on their children education to the school. For that needs to be seen the efforts of parents in the home to develop childrens creativity and cooperation from the parents and teachers. The research design was descriptif qualitatif approach describe the cause and effect, fact and reality about the effort of parents in improving the creativity of tunagrahita child in SLB YPPLB Padang.The sources of the research was parents, headmaster, tutor and teacher. The instument of this research was using interview and picture analysis. Techniques of data collection was using data reduction, data analysis and hypothesis of the research. The result of the interview stated that the effort of parents in improving their children creativity by giving the freedom of choosing the subject f children creativity, respecting their condition, building their emotional approach, appreciating their achievement and supporting them. The parents are also build the opportunity with the teacher by taking and giving the information of the children growth in school and supporting the school program especially related to the children creativity.